2022
DOI: 10.3389/fpls.2022.1005557
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of huanglongbing on fruit yield and quality and on flushing dynamics of Sicilian lemon trees

Abstract: IntroductionThe severe Asian form of huanglongbing (HLB), a vascular disease associated with the phloem-limited bacterium ‘Candidatus Liberibacter asiaticus’, is transmitted by the Asian citrus psyllid (ACP) Diaphorina citri. Disease impacts are known for sweet oranges and acid limes but not lemons.MethodsIn a five-year study (2017–2021) we compared yield and fruit quality between naturally-infected and healthy 5-yr-old trees of Sicilian lemon ‘Femminello’, and shoot phenology on both lemon and ‘Valencia’ oran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(83 reference statements)
2
3
0
Order By: Relevance
“…We recapitulated these findings by testing acetic acid at 10 µg. In agreement with our previous behavioral measurements 2 , 19 , there was no significant difference between male responses to acetic acid (10 µg source dose) or control. Specifically, 74 of 112 tested males responded and spent 5.1 ± 0.3 min in the 10 µg acetic acid treatment and 4.9 ± 0.3 min in the control field of the arena (P = 0.9349, Wilcoxon test).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We recapitulated these findings by testing acetic acid at 10 µg. In agreement with our previous behavioral measurements 2 , 19 , there was no significant difference between male responses to acetic acid (10 µg source dose) or control. Specifically, 74 of 112 tested males responded and spent 5.1 ± 0.3 min in the 10 µg acetic acid treatment and 4.9 ± 0.3 min in the control field of the arena (P = 0.9349, Wilcoxon test).…”
Section: Resultssupporting
confidence: 93%
“…This pathogen parasitizes the phloem and blocks nutrient circulation, thus causing citrus trees to become unproductive 1 . Citrus growers suffer severe losses manifested in reduced fruit quality and production and, ultimately, plant death 2 . It has been demonstrated that CLas induces infected plants to produce an ACP attractant, methyl salicylate 3 , leading to ACP's preference for CLas-infected over healthy plants.…”
Section: Introductionmentioning
confidence: 99%
“…We recapitulated these findings by testing acetic acid at 10 µg. In agreement with our previous behavioral measurements, 19,2 there was no significant difference between male responses to acetic acid (10 µg source dose) or control. Specifically, 74 of Page10 112 tested males responded and spent 5.1 ± 0.3 min in the 10 µg acetic acid treatment and 4.9 ± 0.3 min in the control field of the arena (P = 0.9349, Wilcoxon test).…”
Section: Wilcoxon Test)supporting
confidence: 93%
“…Citrus growers suffer severe losses manifested in reduced fruit quality and production and, ultimately, plant death. 2 It has been demonstrated that CLas induces infected plants to produce an ACP attractant, methyl salicylate 3 , leading to ACP’s preference for CLas-infected over healthy plants. ACP feeds on infected plants, but due to diseased plants’ low nutritional value, the psyllids move to healthy plants to complete feeding, thus vectoring the HLB-causing agent 3 from infected to healthy trees.…”
Section: Introductionmentioning
confidence: 99%
“…The citron fruits typically harvest in November and December, after which they are stored in refrigerated conditions (Adewoyin et al, 2022). Starting in January, the demand for citrus fruits increases, but the quality of the fruit deteriorates over time (Cifuentes et al, 2022). Inadequate storage causes a rapid decline in sugar and ascorbic acid levels.…”
Section: Introductionmentioning
confidence: 99%